Lung oxidative metabolism after exposure to ambient particles - Magnani, Natalia Daniela (2011)
The aim of this work was to study the time course of the oxidative metabolism in mice lung after exposure to ambient particles (ROFA). Swiss mice were intranasally instilled with a ROFA suspension (0.20. mg/kg). Animals were sacrificed 1 or 3. h after the exposure. Eighty percentage of increased oxygen consumption was observed in tissue cubes after 1. h of exposure. This observation was accompanied by an increased NADPH oxidase activity (40%) and mitochondrial oxygen consumption in state 3 (19%). NO production by lung homogenates was found to be increased by 43% after 3. h of exposure. Phospholipid oxidation in lung homogenates showed a 29% increase after 1. h of exposure, while a 30% increase in the carbonyl content was found only after 3. h of exposure. Our data show the relative importance of different sources of reactive oxygen species (NADPH oxidase activity and mitochondrial respiration) to the increased tissue oxygen consumption, oxidative damage and antioxidant status observed in an acute model of ROFA particles exposure.